Social Media for the Promotion of Holistic Self-Participatory Care: An Evidence Based Approach - Miron-Shatz, T.; Hansen, M. M.; Grajales, F. J., III; Martin-Sanchez, F.; Bamidis, P. D. (Yearbook of Medical Informatics, 2013)
Objectives: As health information is becoming increasingly accessible, social media offers ample opportunities to track, be informed, share and promote health. These authors explore how social media and holistic care may work together; more specifically however, our objective is to document, from different perspectives, how social networks have impacted, supported and helped sustain holistic self-participatory care.Methods: A literature review was performed to investigate the use of social media for promoting health in general and complementary alternative care. We also explore a case study of an intervention for improving the health of Greek senior citizens through digital and other means.Results: The Health Belief Model provides a framework for assessing the benefits of social media interventions in promoting comprehensive participatory self-care. Some interventions are particularly effective when integrating social media with real-world encounters. Yet not all social media tools are evidence-based and efficacious. Interestingly, social media is also used to elicit patient ratings of treatments (e.g., for depression), often demonstrating the effectiveness of complementary treatments, such as yoga and mindfulness meditation.Conclusions: To facilitate the use of social media for the promotion of complementary alternative medicine through self-quantification, social connectedness and sharing of experiences, exploration of concrete and abstract ideas are presented here within. The main mechanisms by which social support may help improve health – emotional support, an ability to share experiences, and non-hierarchal roles, emphasizing reciprocity in giving and receiving support – are integral to social media and provide great hope for its effective use.
Keywords: web 2.0; evidence-based health care; community-based participatory research; holistic health; self-management